W-doped niobate-based perovskites: Synthesis by ultrasonic spray pyrolysis and structural characterization - Praxedes, Fabiano R. [UNESP]; Nobre, Marcos A.L. [UNESP]; Olean-Oliveira, André [UNESP]; Teixeira, Marcos F.S. [UNESP]; Poon, Po S.; Lanfredi, Silvania [UNESP]; Matos, Juan (Elsevier, 2023)
Nanostructured hollow spheres composed of K0·5Na0.5(WxNb1-x)O3 were synthesized by ultrasonic spray pyrolysis. Correlations between the W-doping content and properties of the [NbO6] octahedra, including morphology, texture, crystalline structure, and polarization were found. Scanning and transmission electron microscopy analysis indicate the present samples are nanostructured hollow spheres. Textural analysis indicates the samples are composed of a balanced framework including micropores (40–50%) and mesopores (50–60%). Structural refinement by the Rietveld method indicated that non-isovalent W6+ cation only occupies the Nb5+ site in the host structure. Several space groups including Amm2, Pbcm, and Pm were used to refine the W-doped K0·5Na0·5NbO3 structure and the best adjustment was reached assuming the co-existence of two distinct symmetries. The FTIR bands associated with a corner-shared NbO6 octahedron suggested an increase in Nb–O bond length in agreement with the Rietveld refinement. In general, ultrasonic spray pyrolysis is an effective methodology for the one-step synthesis of nanostructured crystallites of W-doped niobate-based perovskites with a tailored structure and morphology.
Keywords: Alkali niobate-based perovskites; Structural characterization; Tungsten-doping; Ultrasonic spray pyrolysis